Digital economy and institutional dynamics: striving for equitable public service in a digitally transformed era - Lyu, Yuwen; Xie, Junxian; Meng, Xulei; Wang, Xiang (Frontiers in Public Health, 2024)
Background The rapid emergence of China’s digital economy has sparked profound interest in the complex interplay between digitalization and the provision of public services. This study aims to delve deeper into how the development of the digital economy impacts the level of equalization in public service delivery and evaluates whether institutional factors can moderate this transformation. Against the backdrop of pursuing “common prosperity,” this research provides valuable guidance for policymaking and strategic planning. It ensures that the ascent of the digital economy not only elevates the standards of public services but also fosters their equitable distribution, thereby advancing the cause of social equity. Methodology The study utilized the System Generalized Method of Moments (GMM) model along with longitudinal trend data spanning from 2009 to 2018. This approach facilitated an in-depth analysis of the relationship between the digital economy and the level of equalization in public service delivery. The application of this model provided deeper insights into the impact of the digital economy on public service equalization and the identification of underlying mechanisms. Findings This study reveals a complex paradox that the digital economy is exacerbating regional disparities in the provision of basic public services. Furthermore, the research underscores the pivotal role of institutional environments in mitigating the adverse effects of the digital economy on public service provision. By examining the interplay between digital economy growth and institutional frameworks, the study suggests that adaptable and robust institutions are essential for harnessing the digital economy’s benefits while minimizing its potential drawbacks. Conclusion In conclusion, the findings from this study offer substantial insights into the dual impact of the digital economy on public service provision, enriching the ongoing discourse on digital transformation and social equity. The research underscores the significance of strategic policy reforms and institutional adjustments to harness the transformative power of the digital economy, promoting equitable access to public services and advancing the goal of “common prosperity” in the digital age.